PENGARUH METODE DISKUSI KASUS KASUS TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG HIV/AIDS DI SMPN 10 KOTA PEMATANGSIANTAR TAHUN 2018 - Sembiring, Ribka Nova Sartika (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Health education of HIV/AIDS for teenagers is important to be done because the incidence rate of HIV/AIDS throughout the world is increasing each year. HIV/AIDS is a public health problem which needs serious attention because this disease spreads rapidly all over the world. Today, each day about 2,000 under 15 year- old children are infected by HIV/AIDS. The research was quasi experimental with one group pretestposttest toward the students’ knowledge and attitude of at SMPN 10, Pematangsiantar. The population was 463 students, and the samples were taken by using simple random sampling technique. The percentage of the average knowledge in the discussion group after the intervention (16.033) was different from the average knowledge in the lecture group (14.433) as it was proved by the result of t-test at p-value = 0.001 < 0.05. The percentage of the students’ average attitude toward HIV/AIDS in the discussion group after the intervention (63.400) was different from the average attitude in the lecture group (53.966) as it was proved by the result of t-test at p-value = 0.000 > 0.05. It was found that discussion method was more effective since discussion method was more able to influence teenagers’ knowledge and attitude. It is recommended that the management of the school develop, and guide the students to use discussion method since it is able to improve their knowledge and attitude toward HIV/AIDS in presenting information and do the fostering about behavior in HIV/AIDS to the students of SMPN 10, Pematangsiantar.